Platinum-carbon catalyst, preparation method thereof and fuel cell

By heat treatment of the platinum carbon catalyst, a catalyst with a high-stability positive charge on the surface was prepared, which solved the problem of uneven distribution of ion polymers, reduced oxygen transport and proton conduction resistance, and improved the performance of fuel cells.

CN119695183AActive Publication Date: 2025-03-25SUZHOU HYDROGINE POWER TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411898203.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing platinum carbon catalysts are unevenly distributed in fuel cells, resulting in an increase in oxygen transport resistance and proton conduction resistance, affecting fuel cell performance.

Method used

By performing heat treatment of 600°C to 700°C under an inert atmosphere, a platinum carbon catalyst with a high stability positive charge on the surface was prepared to make it cover more uniformly with the ionic polymer.

Benefits of technology

It effectively reduces the local oxygen transmission resistance and proton conduction resistance in the catalyst layer, and improves the performance of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005202409600000111
    Figure BDA0005202409600000111
Patent Text Reader

Abstract

The invention discloses a platinum-carbon catalyst, a preparation method thereof and a fuel cell and belongs to the field of fuel cells. The platinum-carbon catalyst comprises a carbon carrier and platinum particles loaded on the carbon carrier, the platinum-carbon catalyst is subjected to heat treatment at 600-700 DEG C for 0.5-3 h in an inert atmosphere, and the Zeta potential of the platinum-carbon catalyst subjected to heat treatment is measured to be larger than 0. In other words, the surface of the platinum-carbon catalyst has stably combined positive charges, so that the covering degree and the covering thickness of an ionic polymer on the surface of the platinum-carbon catalyst are more uniform when the catalyst layer of the fuel cell is prepared, and the local oxygen transmission resistance and the proton conduction resistance in the catalyst layer are effectively reduced; the performance of the fuel cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cells, and in particular, to a platinum-carbon catalyst and a preparation method thereof, and a fuel cell. Background Art

[0002] As a key component of the catalyst layer (CLs) in polymer electrolyte membrane fuel cells (PEMFCS), the surface properties of Pt-C catalysts are believed to have a great influence on mass transport, mainly manifested in the distribution of ionic polymers on the catalyst surface. In the catalyst layer, the redox reaction (ORR) only occurs on the catalytically active sites, where Pt is in direct contact with protons, electrons, and oxygen. Therefore, in order to feed the gaseous reactant oxygen (O 2 ) and ORR product water (H 2 O) provides an effective shorter transport path, and the uniformity and thickness of the ionomer coverage on the catalyst are quite important. Uneven ionomer distribution will not only lead to an increase in local oxygen transport resistance in areas with thicker ionomer membranes, but also increase proton conduction resistance in areas with thinner ionomer membranes. Summary of the invention

[0003] The present application provides a platinum-carbon catalyst, a preparation method thereof, and a fuel cell, wherein the surface of the platinum-carbon catalyst has a highly stable positive charge, which is beneficial for the ion polymer to cover the surface more evenly and in a more thick layer when the catalyst is mixed with the ion polymer, thereby effectively reducing the local oxygen transfer resistance and proton conduction resistance in the catalyst layer and improving the performance of the fuel cell.

[0004] The embodiment of the present application is implemented as follows:

[0005] In a first aspect, the present application provides a platinum-carbon catalyst, which includes a carbon support and platinum particles supported on the carbon support;

[0006] The platinum-carbon catalyst is heat-treated at 600°C-700°C for 0.5-3h under an inert atmosphere, and the Zeta potential of the heat-treated platinum-carbon catalyst is measured to be greater than 0. The surface of the platinum-carbon catalyst provided in the present application has a stable positive charge, so that when the platinum-carbon catalyst is used to prepare the catalyst layer of the fuel cell, it is beneficial for the coverage degree and coverage thickness of the ion polymer on the surface of the platinum-carbon catalyst to be more uniform, thereby effectively reducing the local oxygen transmission resistance and proton conduction resistance in the catalyst layer, and improving the performance of the fuel cell.

[0007] In some optional embodiments, the Zeta potential of the platinum-carbon catalyst is 25 mV-40 mV.

[0008] In some optional embodiments, the pH value of the platinum-carbon catalyst is 6-7; and / or,

[0009] The oxygen content in the platinum-carbon catalyst is 2%-3%; and / or,

[0010] The nitrogen content in the platinum carbon catalyst is 0%.

[0011] In some optional embodiments, the loading amount of platinum particles in the platinum-carbon catalyst is 40%-60%.

[0012] In some optional embodiments, the average particle size of the platinum particles is 2nm-4nm, and the average particle size of the carbon carrier is 20nm-40nm.

[0013] In the second aspect, the present application provides an example of a method for preparing a platinum-carbon catalyst provided in the first aspect of the present application, which comprises:

[0014] The platinum-carbon catalyst to be treated, the electrolyte salt and the solvent are mixed, reacted for 6-24 hours, filtered and dried;

[0015] Among them, the electrolyte salt includes nitrate.

[0016] The preparation method provided in the present application is controllable in operation, and the surface of the prepared platinum-carbon catalyst has a stable positive charge, which is beneficial for making the coverage degree and coverage thickness of the ion polymer on the surface of the platinum-carbon catalyst more uniform when preparing the catalyst layer of the fuel cell, thereby effectively reducing the local oxygen transfer resistance and proton conduction resistance in the catalyst layer and improving the performance of the fuel cell.

[0017] In some optional embodiments, the preparation method further comprises: heat treating the intermediate product obtained by drying at 600° C.-700° C. for 0.5-3 h under an inert atmosphere.

[0018] In some optional embodiments, the electrolyte salt includes at least one of sodium nitrate and potassium nitrate;

[0019] Optionally, the mass ratio of the platinum-carbon catalyst to the electrolyte salt is 1:1-12, optionally 1:1-10.

[0020] In some optional embodiments, the solvent includes at least one of water, methanol, ethanol, and N,N-dimethylfuran.

[0021] In some optional embodiments, the Zeta potential of the platinum-carbon catalyst to be treated is less than 0, and may be -10 mV to -20 mV.

[0022] In a third aspect, the present application provides an example of a fuel cell, which includes a catalyst layer, wherein the catalyst layer includes the platinum-carbon catalyst provided in the first aspect of the present application and an ion polymer. DETAILED DESCRIPTION

[0023] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0024] The following is a detailed description of the platinum-carbon catalyst, its preparation method, and the fuel cell according to the embodiment of the present application:

[0025] In a first aspect, the present application provides a platinum-carbon catalyst, which includes a carbon carrier and platinum particles supported on the carbon carrier.

[0026] The platinum-carbon catalyst is heat-treated at 600° C.-700° C. for 0.5-3 h under an inert atmosphere, and the Zeta potential of the heat-treated platinum-carbon catalyst is measured to be greater than 0.

[0027] It can be understood that here the platinum-carbon catalyst is heat treated at 600°C-700°C under an inert atmosphere for 0.5-3h, and then the Zeta potential of the platinum-carbon catalyst after the heat treatment is detected. The heat treatment here is actually a test condition. Since the detection condition can remove unstable positive charges and will not cause a change in charge performance (for example, from negative to positive), therefore, through the above-mentioned detection conditions, when the test result is that the Zeta potential of the platinum-carbon catalyst after the heat treatment is greater than 0, it can be explained that before the heat treatment, the positive charge is stably bound to the surface of the platinum-carbon catalyst provided in this application.

[0028] It can be understood that since the detection conditions will not cause a change in charge properties (for example, from negative to positive), that is, the surface of the platinum-carbon catalyst before heat treatment has a positive charge (that is, a cation), that is, the Zeta potential of the platinum-carbon catalyst before heat treatment is greater than 0.

[0029] The inert atmosphere includes but is not limited to at least one of nitrogen and argon.

[0030] Illustratively, the temperature of the heat treatment is any one of 600° C., 625° C., 650° C., 675° C., 700° C., or between any two values.

[0031] Exemplarily, the heat treatment time is any one of 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, or between any two values.

[0032] In summary, the surface of the platinum-carbon catalyst provided in the present application has a stable positive charge, which makes it beneficial for the coverage degree and coverage thickness of the ion polymer on the surface of the platinum-carbon catalyst to be more uniform when the platinum-carbon catalyst is used to prepare the catalyst layer of the fuel cell, thereby effectively reducing the local oxygen transfer resistance and proton conduction resistance in the catalyst layer, and improving the performance of the fuel cell.

[0033] In some optional embodiments, the Zeta potential of the platinum-carbon catalyst is 25 mV-40 mV.

[0034] The above-mentioned platinum-carbon catalyst has a high Zeta potential and a large amount of positive charges on its surface, which is beneficial for the ion polymer to have a more uniform surface coverage and thickness on the platinum-carbon catalyst when mixed with the ion polymer, thereby effectively reducing the local oxygen transfer resistance and proton conduction resistance in the catalyst layer and improving the performance of the fuel cell.

[0035] Exemplarily, the Zeta potential of the platinum-carbon catalyst is any one of 25 mV, 26 mV, 28 mV, 30 mV, 32 mV, 35 mV, 37 mV, 40 mV, or between any two values.

[0036] In some optional embodiments, the pH value of the platinum-carbon catalyst is 6-7; and / or, the oxygen content in the platinum-carbon catalyst is 2%-3%; and / or, the nitrogen content in the platinum-carbon catalyst is 0%.

[0037] From the above parameters, it can be seen that the surface of the platinum-carbon catalyst does not contain modified groups such as amino groups, that is, the positive charge on the surface of the platinum-carbon catalyst is not introduced by introducing modified groups such as amino groups.

[0038] In some optional embodiments, the loading amount of platinum particles in the platinum-carbon catalyst is 40%-60%.

[0039] Within the above range, the loading amount of platinum particles in the platinum-carbon catalyst is high, which can meet the usage requirements and is beneficial to improving the catalytic efficiency.

[0040] Exemplarily, the loading of platinum particles in the platinum-carbon catalyst is any value of 40%, 43%, 45%, 48%, 50%, 53%, 55%, 57%, 60%, or between any two values.

[0041] In some optional embodiments, the average particle size of the platinum particles is 2 nm-4 nm, and the average particle size of the carbon carrier is 20 nm-40 nm.

[0042] Under the above parameters, the platinum particles in the platinum-carbon catalyst have a small particle size, the platinum-carbon catalyst has a large specific surface area, and the platinum-carbon catalyst has a better catalytic effect.

[0043] The second aspect of the present application provides a method for preparing the platinum-carbon catalyst provided in the first aspect of the present application, which comprises:

[0044] The platinum-carbon catalyst to be treated, the electrolyte salt and the solvent are mixed, reacted for 6-24 hours, filtered and dried;

[0045] Among them, the electrolyte salt includes nitrate.

[0046] It can be understood that the platinum-carbon catalyst to be treated refers to the platinum-carbon catalyst before being modified by the preparation method of the present application, which can be prepared by itself or directly purchased from the market, and is not limited here.

[0047] The solvent is used to disperse the platinum-carbon catalyst to be treated and dissolve the electrolyte salt. By mixing the platinum-carbon catalyst to be treated, the electrolyte salt and the solvent, the platinum-carbon catalyst and the ionized cations of the electrolyte salt are fully contacted, adsorbed and combined through liquid phase mixing, which is beneficial to the cations to modify the surface of the platinum-carbon catalyst to be treated, and a platinum-carbon catalyst with uniformly distributed positive charges on the surface is obtained as an intermediate product, wherein most of the positive charges in the intermediate product are stably combined on its surface.

[0048] That is to say, the preparation method provided in the present application is controllable in operation, and the surface of the prepared platinum-carbon catalyst has a stable positive charge, which is beneficial to the more uniform coverage and thickness of the ion polymer on the surface of the platinum-carbon catalyst when preparing the catalyst layer of the fuel cell, thereby effectively reducing the local oxygen transfer resistance and proton conduction resistance in the catalyst layer, and improving the performance of the fuel cell.

[0049] In some optional embodiments, the preparation method further comprises: heat treating the intermediate product obtained by drying at 600° C.-700° C. for 0.5-3 h under an inert atmosphere.

[0050] It can be understood that the heat treatment in the preparation method is not a testing method, but a part of the preparation method. Through the above-mentioned heat treatment, the small number of unstable positive charges and impurities on the surface of the intermediate product can be effectively removed without destroying the structure of the platinum-carbon catalyst, so as to obtain a platinum-carbon catalyst with less impurities and more stable Zeta potential. When it is used in a fuel cell, it is beneficial to make the surface coverage and coverage thickness of the ion polymer on the platinum-carbon catalyst more uniform, thereby effectively reducing the local oxygen transfer resistance and proton conduction resistance in the catalyst layer, and improving the performance of the fuel cell.

[0051] The inert atmosphere includes but is not limited to at least one of argon and nitrogen.

[0052] Illustratively, the temperature of the heat treatment is any one of 600° C., 625° C., 650° C., 675° C., 700° C., or between any two values.

[0053] Exemplarily, the heat treatment time is any one of 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, or between any two values.

[0054] The nitrate as the electrolyte salt includes but is not limited to at least one of sodium nitrate, potassium nitrate, lithium nitrate and the like.

[0055] In some optional embodiments, the electrolyte salt includes at least one of sodium nitrate and potassium nitrate.

[0056] The electrolyte salt can be fully ionized in the solvent and has a good effect on modifying the surface positive charge of the treated platinum-carbon catalyst.

[0057] In some optional embodiments, the mass ratio of the platinum carbon catalyst to the electrolyte salt is 1:1-12.

[0058] By adjusting the mass ratio of the two, the Zeta potential of the final platinum-carbon catalyst can be adjusted to have a higher Zeta potential, which is beneficial for the ion polymer to cover the surface of the platinum-carbon catalyst more evenly and with a more uniform thickness when it comes into contact with the ion polymer.

[0059] Illustratively, the mass ratio of the platinum carbon catalyst to the electrolyte salt is any one of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or between any two values.

[0060] Optionally, the mass ratio of the platinum carbon catalyst to the electrolyte salt is 1:1-10.

[0061] In some optional embodiments, the solvent includes at least one of water, methanol, ethanol, and N,N-dimethylfuran.

[0062] The above solvents have a better dispersing effect and can ionize the electrolyte salt to generate cations.

[0063] In some optional embodiments, the zeta potential of the platinum-carbon catalyst to be treated is less than 0.

[0064] It can be understood that the Zeta potential of the to-be-treated platinum-carbon catalyst is less than 0, that is, the surface of the to-be-treated platinum-carbon catalyst has a negative charge (that is, an anion).

[0065] Optionally, the Zeta potential of the platinum-carbon catalyst to be treated is -10 mV to -20 mV.

[0066] The surface of the treated platinum-carbon catalyst with a Zeta potential of -10mV to -20mV adsorbs more negative charges. Therefore, by adjusting the concentration of the electrolyte solution, the conversion of its surface charge can be effectively regulated, which is conducive to obtaining a platinum-carbon catalyst with a higher Zeta potential.

[0067] Exemplarily, the Zeta potential of the platinum-carbon catalyst is any value of -10 mV, -11 mV, -12 mV, -13 mV, -14 mV, -15 mV, -16 mV, -17 mV, -18 mV, -19 mV, -20 mV, or between any two values.

[0068] For example, the zeta potential of the treated platinum-carbon catalyst can be prepared using a chlorine-containing platinum precursor, which has a relatively large negative charge (Cl - ), which is beneficial for the Zeta potential of the prepared platinum-carbon catalyst to reach -10mV to -20mV.

[0069] A third aspect of the present application provides a fuel cell, which includes a catalyst layer, and the catalyst layer includes the platinum-carbon catalyst provided in the first aspect of the present application and an ion polymer.

[0070] The platinum-carbon catalyst, its preparation method and the fuel cell of the present application are further described in detail below in conjunction with the examples.

[0071] In the following examples and comparative examples, the platinum-carbon catalyst to be treated is referred to as the Pt / C catalyst to be treated, and its Zeta potential is -17.63 mV, the Pt loading in the Pt / C catalyst to be treated is 50%, the pH value of the Pt / C catalyst to be treated is 6.8, the oxygen content is 2.8%, the nitrogen content is 0%, the average particle size of the platinum particles is 3 nm, and the average particle size of the carbon carrier is 31 nm.

[0072] Example 1

[0073] A Pt / C catalyst, the preparation method of which comprises:

[0074] 1 g of the Pt / C catalyst to be treated was dispersed in 20 ml of water, and then 20 ml of a 5 mol / L sodium nitrate solution was added (the mass ratio of the Pt / C catalyst to sodium nitrate (NaNO 3 :Pt / C) is 8.5), stirred for 12 hours, filtered and washed, and the obtained solid was placed in a vacuum drying oven at 80°C to dry to obtain an intermediate product.

[0075] The intermediate product was heat treated at 700°C for 3 h under an argon atmosphere to obtain a Pt / C catalyst.

[0076] Example 2

[0077] A Pt / C catalyst, the preparation method of which comprises:

[0078] 1 g of the Pt / C catalyst to be treated was dispersed in 20 ml of water, and then 20 ml of a 7 mol / L sodium nitrate solution (the mass ratio of Pt / C catalyst to sodium nitrate (NaNO 3 :Pt / C) is 11.9), and after stirring for 12 hours, the obtained solid is filtered and washed, and placed in a vacuum drying oven at 80°C to dry to obtain an intermediate product.

[0079] The intermediate product was heat treated at 700°C for 3 h under an argon atmosphere to obtain a Pt / C catalyst.

[0080] Example 3

[0081] A Pt / C catalyst, the preparation method of which comprises:

[0082] 1 g of the Pt / C catalyst to be treated was dispersed in 20 ml of water, and then 20 ml of a 3 mol / L sodium nitrate solution (the mass ratio of Pt / C catalyst to sodium nitrate (NaNO 3 :Pt / C) is 5.1), stirred for 12 hours, filtered and washed, and the obtained solid was placed in a vacuum drying oven at 80°C to obtain an intermediate product.

[0083] The intermediate product was heat treated at 700°C for 3 h under an argon atmosphere to obtain a Pt / C catalyst.

[0084] Example 4

[0085] A Pt / C catalyst, the preparation method of which comprises:

[0086] 1 g of the Pt / C catalyst to be treated was dispersed in 20 ml of water, and then 20 ml of 1 mol / L sodium nitrate solution (the mass ratio of Pt / C catalyst to sodium nitrate (NaNO 3 :Pt / C) is 1.7), stirred for 12 hours, filtered and washed, and the obtained solid was placed in a vacuum drying oven at 80°C to obtain an intermediate product.

[0087] The intermediate product was heat treated at 700°C for 3 h under an argon atmosphere to obtain a Pt / C catalyst.

[0088] Example 5

[0089] A Pt / C catalyst, the preparation method of which comprises:

[0090] 1 g of the Pt / C catalyst to be treated was dispersed in 20 ml of N,N-dimethylfuran, and then 20 ml of a 5 mol / L sodium nitrate solution was added (the mass ratio of Pt / C catalyst to sodium nitrate (NaNO 3 :Pt / C) is 8.5), stirred for 12 hours, filtered and washed, and the obtained solid was placed in a vacuum drying oven at 80°C to dry to obtain an intermediate product.

[0091] The intermediate product was heat treated at 600°C for 1 h under an argon atmosphere to obtain a Pt / C catalyst.

[0092] Comparative Example 1

[0093] 1 g of the Pt / C catalyst to be treated was heat treated at 700° C. for 3 h in an argon atmosphere to obtain a Pt / C catalyst.

[0094] Among them, the Zeta potential of the Pt / C catalyst test is <0, specifically -12.53 mV.

[0095] That is to say, although heat treatment alone can improve the Zeta potential of the Pt / C catalyst, its Zeta potential is still negative, that is, heat treatment alone has no substantial effect on the charge on the surface of the Pt / C catalyst.

[0096] Comparative Example 2

[0097] Disperse 1 g of the Pt / C catalyst to be treated in 20 ml of water, then add 20 ml of 5 mol / L nitric acid solution, stir at 80°C for 3 h, filter and wash, and dry the obtained solid in a vacuum drying oven at 80°C to obtain an intermediate product. The Zeta potential of the intermediate product is tested to be >0, specifically 12.61 mV.

[0098] The intermediate product was heat treated at 700° C. for 3 h under an argon atmosphere to obtain a Pt / C catalyst with a Zeta potential of <0 (specifically −7.36 mV).

[0099] According to Comparative Example 2, it can be seen that when the Pt / C catalyst is treated with a nitric acid solution, the charge adsorption is unstable.

[0100] Comparative Example 3

[0101] A Pt / C catalyst, the preparation method of which comprises:

[0102] 1 g of the Pt / C catalyst to be treated was dispersed in 20 ml of water, and then 20 ml of a 5 mol / L sodium chloride solution was added thereto. After stirring for 12 hours, the mixture was filtered and washed. The obtained solid was placed in a vacuum drying oven at 80°C and dried to obtain an intermediate product.

[0103] The intermediate product was heat treated at 700° C. for 3 h under an argon atmosphere to obtain a Pt / C catalyst with a Zeta potential of <0 (specifically −2.53 mV).

[0104] According to Comparative Example 3, it can be seen that the Cl - The electrolyte solution has strong negative charge adsorption, which will weaken the modification effect of positive potential.

[0105] Test Example 1

[0106] The Pt / C catalyst used as a raw material in each embodiment and comparative example was used as a basic control group, and the relevant parameters and Zeta potential of the Pt / C catalysts prepared in the basic control group and embodiments 1-5 and comparative examples 1-3 were tested.

[0107] The specific test method of the Zeta potential of the Pt / C catalyst is as follows: a certain amount of Pt / C catalyst is dispersed in water, and after ultrasonication for 10 minutes, the Zeta potential is tested using a CMX particle potentiometric titration analyzer from the German ColloidMetrix company. The test temperature is 25°C, and each sample is measured three times to take the average value.

[0108] Among them, the Pt loading in the Pt / C catalyst in Examples 1-5 and Comparative Examples 1-3 is 50%, the pH value is 6.8, the nitrogen content is 0%, the average particle size of the carbon carrier is 31 nm, and the Zeta potential test results of the Pt / C catalyst as well as the oxygen content and the average particle size of the platinum particles change. The specific test results are shown in Table 1.

[0109] Table 1 Zeta potential test results of Pt / C catalyst, oxygen content and average particle size of platinum particles

[0110]

[0111] It can be seen from Table 1 that the preparation method provided in the present application can prepare a platinum-carbon catalyst having a positive charge on the surface with high stability.

[0112] According to the comparison of Examples 1-4, it can be seen that the increase in the concentration of sodium nitrate can further increase the value of the surface charge Zeta potential, but when its concentration is 5 mol / L and above, even if its concentration is further increased, the Zeta potential value is basically constant, so the sodium nitrate concentration of Example 1 is preferred.

[0113] Test Example 2

[0114] Perfluorosulfonic acid ionomer adsorption experiment:

[0115] The self-adsorption capacity of the catalyst and the ionomer is determined by a perfluorosulfonic acid ionomer adsorption experiment. The specific operation includes: soaking 100 mg of the Pt / C catalyst of each embodiment and the comparative example in a perfluorosulfonic acid (PFSA) ionomer aqueous solution with a mass concentration of 24% to 25%, stirring for 30 minutes, and separating the Pt / C catalyst after standing and settling, and drying the dried Pt / C catalyst. If the mass of the Pt / C catalyst increases by 5% to 50%, it means that the Pt / C catalyst has a certain self-adsorption capacity for the PFSA ionomer. If the mass increase of the Pt / C catalyst is less than 5%, it means that there is no self-adsorption capacity for the PFSA ionomer.

[0116] Oxygen transmission test:

[0117] The Pt / C catalysts prepared in the above-mentioned embodiments and comparative examples were used to prepare single cells.

[0118] A single cell with an active area of ​​5 cm2 was analyzed using a model 850e fuel cell test system (Scribner, USA). Pt / C catalyst, deionized water, isopropanol, and 5% (weight) Nafion were mixed into a slurry by shearing. The Pt / C catalyst slurry was sprayed on the cathode by ultrasonic spraying, and a commercial 50wt% Pt / C was used for the anode. Pt was added at 0.1 mg / cm 2 The content is loaded on the cathode and anode.

[0119] The limiting current density test was performed on a single cell that had been activated with 100% humidity. The battery operating conditions and test steps are as follows: 1. Stable conditions: at 0.7V, 0.5slpm hydrogen at the anode and 1.0slpm nitrogen-oxygen mixture at the cathode, stabilize for 30 minutes. 2. Constant potential load test limiting current, stabilize for 5 minutes at 0.7V, start at 0.4V, test every 0.1V, and stabilize for 5 minutes at each point from 0.4V to 0.1V. Test each curve twice and record the data. 3. Under a certain pressure, perform polarization curve tests of the above voltage modes with different oxygen concentrations, and the cathode gas oxygen concentration test order is from low to high. (The cathode is an oxygen-nitrogen mixture with oxygen concentrations of 1%, 2%, and 3%, respectively)

[0120] Data processing:

[0121] 1. Plot the graph with oxygen concentration as the horizontal axis and the measured value of limiting current density as the vertical axis. The slope of the straight line is inversely proportional to the total oxygen transmission resistance value Rtotal.

[0122] Where, Rtotal = 4FP / RT*1 / b;

[0123] Rtotal—oxygen transfer resistance;

[0124] b—the slope of the graph of limiting current density and oxygen concentration;

[0125] F—Faraday constant (96485C / mol);

[0126] R—gas constant (8.314 Jmol-1k-1);

[0127] T—battery temperature;

[0128] P—absolute pressure value.

[0129] The more uniform the ionomer coverage and the more uniform the thickness, the smaller the corresponding oxygen transmission resistance. Therefore, the smaller the oxygen transmission resistance, the more uniform the ionomer coverage and the more uniform the thickness.

[0130] The test results are shown in Table 2.

[0131] Table 2 Test results

[0132] Mass increase after adsorption experiment Oxygen transfer resistance / s / cm Example 1 50% 0.66 Example 2 50% 0.68 Example 3 30% 0.78 Example 4 10% 0.83 Example 5 35% 0.75 Comparative Example 1 0% 1.02 Comparative Example 2 2% 0.93 Comparative Example 3 5% 0.93

[0133] It can be seen from the data in Table 2 that compared with the comparative example, the mass increase of the platinum-carbon catalyst in the embodiment of the present application is significantly increased and the oxygen transfer resistance is significantly reduced after the adsorption experiment. That is, after the platinum-carbon catalyst in the embodiment of the present application is mixed with the ion polymer, it is beneficial to make the surface coverage and coverage thickness of the ion polymer on the platinum-carbon catalyst more uniform, effectively reduce the local oxygen transfer resistance in the catalyst layer, and improve the performance of the fuel cell.

[0134] According to Examples 1-4, the higher the Zeta potential of the surface of the platinum-carbon catalyst, the greater the density of positive charges on its surface, and the more perfluorosulfonic acid ionomers adsorbed by the Coulomb force between positive and negative charges, resulting in a smaller oxygen transfer resistance in the single cell, and the corresponding ionomer coverage tends to be more uniform.

[0135] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A platinum-carbon catalyst, characterized in that It includes a carbon carrier and platinum particles supported on the carbon carrier; The platinum-carbon catalyst is heat-treated at 600° C.-700° C. for 0.5-3 h under an inert atmosphere, and the Zeta potential of the platinum-carbon catalyst after the heat treatment is measured to be greater than 0.

2. The platinum-carbon catalyst according to claim 1, characterized in that The Zeta potential of the platinum-carbon catalyst after heat treatment is 25 mV-40 mV.

3. The platinum-carbon catalyst according to claim 1, characterized in that The pH value of the platinum-carbon catalyst is 6-7; and / or; The oxygen content of the platinum-carbon catalyst is 2%-3%; and / or, The nitrogen content in the platinum-carbon catalyst is 0%.

4. The platinum-carbon catalyst according to claim 1, characterized in that The loading amount of the platinum particles in the platinum-carbon catalyst is 40%-60%.

5. The platinum-carbon catalyst according to claim 1, characterized in that The average particle size of the platinum particles is 2nm-4nm, and the average particle size of the carbon carrier is 20nm-40nm.

6. A method for preparing a platinum-carbon catalyst as claimed in any one of claims 1 to 5, characterized in that: include: The platinum-carbon catalyst to be treated, the electrolyte salt and the solvent are mixed, reacted for 6-24 hours, filtered and dried; Wherein, the electrolyte salt comprises nitrate.

7. The preparation method according to claim 6, characterized in that: The preparation method further comprises: heat treating the intermediate product obtained by drying at 600° C.-700° C. for 0.5-3 h under an inert atmosphere.

8. The preparation method according to claim 6, characterized in that: The electrolyte salt includes at least one of sodium nitrate and potassium nitrate; Optionally, the mass ratio of the platinum-carbon catalyst to the electrolyte salt is 1:1-12, and may be 1:1-10; Optionally, the solvent includes at least one of water, methanol, ethanol, and N,N-dimethylfuran.

9. The preparation method according to claim 6, characterized in that: The Zeta potential of the platinum-carbon catalyst to be treated is less than 0, and can be selected to be -10mV to -20mV.

10. A fuel cell, characterized in that: The catalyst layer comprises a catalyst layer, wherein the catalyst layer comprises the platinum-carbon catalyst according to any one of claims 1 to 5 and an ion polymer.

Citation Information

Patent Citations

  • A high oxygen transport fuel cell catalytic layer and a membrane electrode assembly and a fuel cell

    CN109103472A

  • Bifunctional modified platinum-carbon catalyst and preparation method thereof

    CN114583195A

  • Method for regulating and controlling membrane electrode catalyst layer by positively charged carbon dots and application thereof

    CN115101765A

  • Fuel cell pure water-based catalyst slurry and preparation method thereof

    CN115241467A

  • Carbon carrier for fuel cell and preparation and application of platinum-based catalyst of carbon carrier

    CN116598515A